Effects of polycyclic aromatic hydrocarbons on the proliferation and differentiation of placental cells - Yun Sung Jo; Hyun Sun Ko; Ah Young Kim; Ha Gyeong Jo; Woo Jung Kim; Sae Kyung Choi (BMC, 2022)
Abstract Background The purpose of this study was to investigate the effects of polycyclic aromatic hydrocarbons (PAHs) other than bisphenol A (BPA) and BPA substitutes on placental cells. Methods HTR-8/SVneo cells were treated with anthracene, benzo[k]fluoranthene, benzo[a]pyrene, and 4,4-(9-fluorenylidene)diphenol, which is used as a substitute for BPA-free products. After confirming the dose response for each reagent using the prepared cells, the cells were incubated for 24, 48, and 72 h. Cell viability was confirmed using the XTT assay. Each experiment was performed with the minimum number of samples (n = 3) required for statistical analysis. The results were analyzed using t-tests; p < 0.05 was considered statistically significant. Results After treatment with anthracene, benzo[k]fluoranthene, benzo[a]pyrene, and 4,4-(9-fluorenylidene)diphenol, the absorbance measured using the XTT assay decreased significantly with increasing concentration. The absorbance decreased significantly over time following treatment with each endocrine disruptor at the concentration confirmed by the dose-response analysis. Conclusions This study showed that anthracene, benzo[k]fluoranthene, benzo[a]pyrene, and 4,4-(9-fluorenylidene)diphenol-a BPA substitute-affect cell viability and necrosis in the placental cell line. The study indicates the serious effects of PAHs that negatively affect pregnancy but were previously unknown. Further, this study would serve as a reference for the identification of harmful PAHs during pregnancy prognosis in women who are more susceptible to PAH exposure.